The Persistent Ionospheric Responses Over Japan After the Impact of the 2011 Tohoku Earthquake - Min‐Yang Chou; Iurii Cherniak; Charles C.H. Lin; N.M. Pedatella (Space Weather)
Abstract In this study, we report the persistent impacts of the 2011 Tohoku earthquake/tsunami on the ionosphere using the ground‐based Global Navigation Satellite System and FORMOSAT‐3/COSMIC total electron content. Multiple unusual ionospheric phenomena, such as ionospheric irregularities, nighttime medium‐scale traveling ionospheric disturbances (MSTIDs), and planar traveling ionospheric disturbances (TIDs), were observed after the emergence of tsunami‐induced concentric gravity waves. The ionospheric irregularities initially developed over the Hokkaido region following the interference of gravity waves at ~8:45 UT. Remarkably, the Perkins‐type nighttime MSTIDs accompanying the planar TIDs were discernible over Japan following the irregularities. By comparing with the tsunami model simulation and ocean buoy observations, it is determined that these planar TIDs, lasting for about 10 hr, were likely related to tsunami ocean waves reflected by seamounts, ridges, islands, and seafloor topography in the Pacific Ocean. Due to the absence of sporadic E layers, we suggest that the coupling between the tsunami‐generated gravity waves and the Perkins instability plays an essential role in initiating the equinoctial nighttime MSTIDs. The long‐lasting tsunami can continuously impact the ionosphere, affecting the nighttime ionospheric electrodynamics and making the conditions conducive for the development of midlatitude nighttime ionospheric irregularities and instabilities.